Navigating Digital Horizons: A Bibliometric Exploration of Digitalization in Family Businesses and Emerging Research Agendas - Saputra, Steven Agung Jaya; Tofani, Muhammad Rizky Uno; Risma, Nadiah; Aisyah, Nur; Kesuma, Muhammad Ramadhani (Ekopedia: Jurnal Ilmiah Ekonomi, 2025)
Digitalization has become a strategic imperative for family businesses as they navigate the challenges of Industry 4.0, shifting market dynamics, and post-pandemic recovery. Despite the growing relevance of digital transformation, existing research on this topic remains fragmented and lacks a comprehensive understanding of its intellectual and thematic evolution. This study aims to map the development of scientific publications on digitalization in family businesses, identify dominant research themes, and outline emerging research directions related to technologies such as artificial intelligence (AI) and sustainability. Using the Scopus database, a bibliometric approach was applied to analyze publication trends, geographic distribution, co-authorship networks, and keyword co-occurrence patterns over the last decade. The results reveal significant growth in publication volume, with research concentrated in advanced economies and increasingly influenced by China’s expanding collaboration network. Six major thematic clusters emerged, highlighting topics such as sustainability orientation, human capital, governance, Industry 4.0 technologies, and the catalytic effects of COVID-19 on digital adoption. These findings demonstrate that digital transformation in family firms is not merely technological, but deeply shaped by socio-emotional, governance, and cultural dimensions. Overall, this study provides a comprehensive research landscape and offers a forward-looking agenda to support more inclusive and sustainable digitalization in family businesses.